2021
DOI: 10.23876/j.krcp.20.224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of residential greenness on clinical outcomes of patients with chronic kidney disease: a large-scale observation study

Abstract: Background As industrialization and urbanization are accelerating, the distribution of green areas is decreasing, particularly in developing countries. Since the 2000s, the effects of surrounding greenness on self-perceived health, including physical and mental health, longevity, and obesity have been reported. However, the effects of surrounding green space on chronic kidney disease are not well understood. Therefore, we investigated the impact of residential greenness on the mortality of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Korean studies based on the National Health Insurance System also showed that exposure to heat and air pollutants increases hospital admissions related to kidney disease [ 16 , 33 ]. Furthermore, previous studies suggested that the beneficial effects of green space on cardiovascular diseases [ 12 , 34 ], which are major causes of kidney diseases, should be majorly addressed in the beneficial roles of greenness on kidney health [ 19 , 25 ]. These results from multiple studies support biological mechanisms and epidemiological evidence of the beneficial effects of greenness on kidney health.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Korean studies based on the National Health Insurance System also showed that exposure to heat and air pollutants increases hospital admissions related to kidney disease [ 16 , 33 ]. Furthermore, previous studies suggested that the beneficial effects of green space on cardiovascular diseases [ 12 , 34 ], which are major causes of kidney diseases, should be majorly addressed in the beneficial roles of greenness on kidney health [ 19 , 25 ]. These results from multiple studies support biological mechanisms and epidemiological evidence of the beneficial effects of greenness on kidney health.…”
Section: Discussionmentioning
confidence: 99%
“…James et al [ 23 ] designed the study to examine the association between green space and various causes of mortality, not only for kidney disease-related deaths. The cohort study of Park et al [ 25 ] was based on a large-scale prospective cohort, but covered patients enrolled at metropolitan hospitals, thus there were limitations in addressing nonmetropolitan areas, particularly rural areas which are generally more vulnerable to medical services [ 36 ]. Paoin et al [ 28 ] also conducted a prospective cohort study; however, their study included only employees in a certain company with limited age distribution (25 to 55 years), thus the generalizability of the study result may be less than in other population-based or multilocation cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations